The Impact of Sulfur Compounds Functioning as Organic Pollutants on the Corrosion of Carbon Steel in Concentration Cells - Abbas, Suzan T.; Alzuraiji, Sahir M.; Hasan, Basim O. (Journal of Petroleum Research and Studies, 2025)
Corrosion is a major challenge in the petroleum industry, influenced by internal fluid conditions and external factors. Concentration cell corrosion occurs when metals interact with solutions of varying concentrations, often exacerbated by sulfur-containing contaminants. This study explores the effects of mercaptoethanol (ME, C₂H₆OS), a sulfur compound commonly found in refinery effluents, on the corrosion behavior of carbon steel (CS) at different temperatures and concentrations. The findings highlight ME's strong influence on corrosion dynamics, demonstrating that both concentration and temperature are crucial factors. At 25 °C, the corrosion rate notably decreased from 5.594 gmd to 3.705 gmd as the ME concentration increased from 1 ml/l to 3 ml/l. Similarly, at 32 °C, while the rate dropped from 4.877 gmd to 4.502 gmd (ME increased 1 ml/l to 2 ml/l), it showed a slight increase to 4.701 gmd at 3 ml/l. Remarkably, at higher temperatures of 40 °C and 50 °C, the corrosion rate jumped from 6.954 gmd to an astonishing 16.267 gmd (ME increased from 1 ml/l to 2 ml/l) before declining to 4.002 gmd and 5.785 gmd at 3 ml/l, respectively. Additionally, the electrochemical potential of CS in the presence of mercaptoethanol shifted negatively with rising temperatures, indicating the formation of a protective surface film. This behavior contrasts with that observed with 0.1 N NaCl, where oxide films form as temperatures increase. These compelling findings emphasize the complex relationship between concentration, temperature, and corrosion mechanisms within concentration cells. These findings highlight mercaptoethanol's advantage over NaCl in mitigating galvanic corrosion in industrial applications.